Модель функціонування ринку підприємств лісового господарства в умовах інноваційного розвитку (Економічний часопис Волинського національного університету імені Лесі Українки, 2018)
It is stated efficient activity of forest enterprises on the market, under its variable conditions and optimal use of forest resources can be modeled by production dynamic linear problem of optimal planning in the article. It is proved at any important element of dynamic model of forest enterprises market development is the system of restrictions, which lies at any moment of time depending on market situation, size of forest resources and existence of diversified possibilities of their use.
Keywords: модель, підприємства лісового господарства, виробничі витрати, інноваційний розвиток